2016
DOI: 10.1016/j.phrs.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor variation affects prostate cancer progression and drug resistance

Abstract: Significant therapeutic progress has been made in treating prostate cancer in recent years. Drugs such as enzalutamide, abiraterone, and cabazitaxel have expanded the treatment armamentarium, although it is not completely clear which of these drugs are the most-effective option for individual patients. Moreover, such advances have been tempered by the development of therapeutic resistance. The purpose of this review is to summarize the current literature pertaining to the biochemical effects of AR variants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 90 publications
(167 reference statements)
0
35
0
Order By: Relevance
“…3 However, many patients exhibit resistance to androgen deprivation therapy, resulting in mCRPC (metastatic castrate-resistant prostate cancer). 4 The patients with mCRPC have poor survival, suggesting that understanding the mechanism of prostate cancer development and progression is pivotal for discovery of new therapies of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, many patients exhibit resistance to androgen deprivation therapy, resulting in mCRPC (metastatic castrate-resistant prostate cancer). 4 The patients with mCRPC have poor survival, suggesting that understanding the mechanism of prostate cancer development and progression is pivotal for discovery of new therapies of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Flutamide and bicalutamide have been proven to have agonist properties in cells engineered to express higher AR levels (Tran et al 2009). Clones with AR gene amplification are commonly induced in vivo by long-term antiandrogen exposure (McCrea et al 2016).…”
Section: First-generation Antiandrogens Withdrawal Syndromementioning
confidence: 99%
“…Two different phase III trials demonstrated the efficacy of enzalutamide in the treatment of CRCP, both before (Beer et al 2014) and after (Scher et al 2012) docetaxel use. Many different mechanisms have been associated with primary and acquired resistance to enzalutamide (McCrea et al 2016). The development of aberrant truncated AR variants, such as ARV-7 and ARV-567, seems to play a central role in CRCP progression (Buttigliero et al 2015).…”
Section: Enzalutamide Withdrawal Syndrome (Ews)mentioning
confidence: 99%
See 2 more Smart Citations